I Тhink, Therefore I Think the Other: Derrida’s Poetics of Hospitality: Мислам, значи, го мислам другото: Деридаовата поетика на гостоприемство - Blagojević, Jelisaveta; Kirkova, Anastazija; Mitrevska, Tatjana (Identities: Journal for Politics, Gender and Culture, 2004)
Author(s): Jelisaveta Blagojević | Јелисавета Благојевиќ Title (English): I Тhink, Therefore I Think the Other: Derrida’s Poetics of Hospitality Title (Macedonian): Мислам, значи, го мислам другото: Деридаовата поетика на гостоприемство Translated by (Serbian to English): Anastazija Kirkova | Анастазија Киркова Translated by (Serbian to Macedonian): Tatjana Mitrevska | Татјана Митревска Journal Reference: Identities: Journal for Politics, Gender and Culture, Vol. 3, No. 2 (Winter 2004) Publisher: Research Center in Gender Studies - Skopje and Euro-Balkan Institute Page Range: 223-235 Page Count: 12 Citation (English): Jelisaveta Blagojević, “I Тhink, Therefore I Think the Other: Derrida’s Poetics of Hospitality,” translated from the Serbian by Anastazija Kirkova, Identities: Journal for Politics, Gender and Culture, Vol. 3, No. 2 (Winter 2004): 223-235. Citation (Macedonian): Јелисавета Благојевиќ, „Мислам, значи, го мислам другото: Деридаовата поетика на гостоприемство“, превод од српски Татјана Митревска, Идентитети: списание за политика, род и култура, т. 3, бр. 2 (зима 2004): 223-235.